Reading for peace? Literature as activism – an investigation into new literary ethics and the novel - Shady E. Cosgrove (University of Wollongong, 2023)
Literary ethicists like Dorothy J Hale and narratologists like James Phelan have argued that the reading process makes literary novels worthy of ethical investigation. That is, it’s not just a book’s content – which may debate norms and values – but the process of reading that inspires the reader to consider Other points of view. This alterity, new ethicists argue, can lead to increased empathy and thus more thoughtful decision-making within the ‘actual’ world. In fact, Hale (2007: 189) says empathetic literary training is a ‘pre-condition for positive social change’. This may work well theoretically, but what practical issues does it hold for social activists? How useful can literature actually be in the face of dire social issues? Can we ‘read’ our way out of poverty and aggressive military intervention? And what would it mean to develop an activism based on reading and empathy? This paper will examine these questions using a framework based on the work of Hale and Phelan. (Hale, 2007)